Varicella-zoster virus VLT-ORF63 fusion transcript induces broad viral gene expression during reactivation from neuronal latency - Werner J. D. Ouwendijk (Nature Portfolio, 2020)
Varicella-zoster virus (VZV) establishes lifelong neuronal latency in humans. Here, Ouwendijk and Depledge et al. identify a fusion transcript, VLT-ORF63, which is expressed during lytic and latent infection, and demonstrate a role for the translated fusion protein in induction of lytic gene expression from latent VZV genomes.